2020
DOI: 10.1098/rsos.200249
|View full text |Cite
|
Sign up to set email alerts
|

Turning defence into offence? Intrusion of cladoceran brood chambers by a green alga leads to reproductive failure

Abstract: Microalgae are the foundation of aquatic food webs. Their ability to defend against grazers is paramount to their survival, and modulates their ecological functions. Here, we report a novel anti-grazer strategy in the common green alga Chlorella vulgaris against two grazers, Daphnia magna and Simocephalus sp. The algal cells entered the brood chamber of both grazers, presumably using the brood current generated by the grazer's abdominal ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…This suggests that in addition to nanoplastics, other exogenous substances ( e.g. , microplastics, colloidal minerals, and microalgae) could also enter the brood chamber from external environments, thus likely leading to direct damage to the developing embryos.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that in addition to nanoplastics, other exogenous substances ( e.g. , microplastics, colloidal minerals, and microalgae) could also enter the brood chamber from external environments, thus likely leading to direct damage to the developing embryos.…”
Section: Resultsmentioning
confidence: 99%
“…It is found that plastic particles of 250 nm and 10 μm could enter the brood chamber through its opening (SI, Figures S21, S22). This suggests that in addition to nanoplastics, other exogenous substances (e.g., microplastics, colloidal minerals, and microalgae) could also enter the brood chamber from external environments, 37 thus likely leading to direct damage to the developing embryos.…”
Section: Resultsmentioning
confidence: 99%